SISTEM PENGAWASAN INTERN ATAS PENERIMAAN DAN PENGELUARAN KAS PADA PT.BANK RAKYAT INDONESIA (PESERO),Tbk. UNIT PULO BRAYAN MEDAN - Marchelina, Syaharman (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2020)
This study aims to determine PT. Bank Rakyat Indonesia (Persero), Tbk. Pulo Brayan Unit Medan. The formulation of the problem in this study is how the Internal Control System for Cash Receipts and Disbursements at PT. Bank Rakyat Indonesia (Persero), Tbk. Medan Pulo Brayan Unit. From the results of this study it can be seen from the total cash receipts and disbursements in 2010 that it is very clear that an internal control system is needed to avoid fraud. Internal Control System for Cash Receipts and Disbursements at PT. Bank Rakyat Indonesia (Persero), Tbk. Medan Pulo Brayan Unit has not been fully effective in carrying out internal oversight of cash receipts. Seen from the duties and responsibilities carried by the teller who often performs multiple tasks, because the teller can perform the task of receiving and spending money and inputting data to the computer. This can make an oversight system ineffective. In addition, this company does not make cash deposits every day at the branch office. While the internal control system for cash disbursements has been effective because it is carried out entirely based on authorization from the branch office to determine the amount of operational costs to be incurred. Suggestions proposed by researchers for companies to make the separation of duties and responsibilities clearly to avoid any deviation from the person himself.